KEPENTINGAN PEMERINTAHAN INDONESIA MEMPERPANJANG KERJASAMA DENGAN PT.FREEPORT INDONESIA TAHUN 2017 - Agus Riadi; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study discusses the interests of Indonesia Extend Cooperation With PT. Freeport Indonesia Year 2017. First Working Contract is from 196 7 until August 2017. Freeport is a mining company from the United States that manages Gold, Metals and Copper (molybdenum). Starting from the mountains of Papua, Indonesia, to the deserts of the Southwest of the United States, the magnificent volcano in Peru, the traditional copper-producing region of Chile and new opportunities in the Democratic Republic of Congo. This study used qualitative research methods. Describing the research by collecting data from various sources from books, journals, and the internet, then collected into a study. The theory used in this research is the theory of national interest according to Donald E. Nucherlain. The results of this study conclude that the interests of Indonesia extend cooperation with PT.Freeport Indonesia is sebai follows: The first legal basis that can be used is a contract of work but after the renewal will be converted into a special permit Business License. The Second Divestment of PT. Freeport Indonesia of 51% for Indonesian ownership, Third construction of refining facility or smelter for five years or not later than 2022, unless there is condition of Force Majeur. Fourth Stability of State Revenue supported by Fiscal and Legal Guarantees documented for PT. Freeport Indonesia.Keywords: Freeport McMoRan,Theory of National Interest, Freeport Indonesia